1996
DOI: 10.33584/jnzg.1996.58.2212
|View full text |Cite
|
Sign up to set email alerts
|

Caucasian clover as a pasture legume for dryland dairying in the coastal Bay of Plenty

Abstract: The ability to spread underground through rhizomes, retention of a strong tap-root and a reputation for pest and disease tolerance, make caucasian clover (Trifolium ambiguum Bieb.) (CC) an attractive possibility for improving legume performance in coastal Bay of Plenty dryland dairying pasture. Large plots (0.125 ha) of Grasslands Kopu white clover (T. repens) (WC) and Endura CC were sown in spring (September 1994) as pure species swards following maize cropping and all but one 7 m wide strip undersown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 11 publications
1
30
2
Order By: Relevance
“…Dinitrogen fixation values presented herein are the first reported estimates of seeding‐year N 2 fixation in kura clover. They are consistent with the report by Watson et al (1996) of almost nil dinitrogenase activity levels in kura clover nodules. Although kura clover N 2 fixation appears to be insignificant in the seeding year, Seguin et al (2000) reported postseeding year N 2 fixation levels to be similar to those of birdsfoot trefoil.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Dinitrogen fixation values presented herein are the first reported estimates of seeding‐year N 2 fixation in kura clover. They are consistent with the report by Watson et al (1996) of almost nil dinitrogenase activity levels in kura clover nodules. Although kura clover N 2 fixation appears to be insignificant in the seeding year, Seguin et al (2000) reported postseeding year N 2 fixation levels to be similar to those of birdsfoot trefoil.…”
Section: Resultssupporting
confidence: 93%
“…Inoculation of kura clover in North America and New Zealand is recommended because few soils outside of its center of origin in the Caucasus contain effective indigenous rhizobia (Hely, 1957). Even when inoculated, there are indications that kura clover has very low N 2 fixation in the establishment year (Watson et al, 1996; Genrich et al, 1998); thus, its initial growth might be N limited. Patrick and Lowther (1995) reported a strong correlation between nodulation and establishment of kura clover.…”
mentioning
confidence: 99%
“…1). GG numbers initially increased more rapidly in WC, probably reflecting greater pasture growth and clover content in year 1 (Watson et al 1996a), but also declined more rapidly in WC plots in year 4. This related to the loss of clover cover and more extreme soil temperatures during summer drought (Watson et al 1998).…”
Section: Results and Discussion Insect Pestsmentioning
confidence: 96%
“…The establishment and conduct of the trials has been described elsewhere (Watson et al 1996a;. Briefly, 0.125 hectare plots × 4 replicates each of cv.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation